Gut hormones in adaptation. (1987) - Bloom, S R
Abstract : The presence of a circulating factor affecting gut growth can be surmised from the findings in gut isolated from the main food stream and not under direct nutritional influence. Thus when a Thiry Vella fistula is constructed and the crypt cell production rate counted in the fistula it can be shown to correlate with the degree of resection of the main bowel left in continuity. The only hormones which become raised in a similar pattern are enteroglucagon and peptide tyrosine tyrosine (PYY). Enteroglucagon has been shown to be part of preproglucagon, which contains in addition oxyntomodulin, glucagon like peptide 1 1-37 and 6-36NH2 and glucagon like peptide 2. These form the main candidates for the 'hormone of gut growth'. Peptide tyrosine tyrosine has been tested by direct administration over 12 days, matching the natural rise, but no affect on crypt cell production rate was seen. Glucagon like peptide 1 1-37 was similarly tested and also found to produce no effect. It remains to test the other members of the glucagon family to confirm or refute the hypothesis that one of them is the enigmatic small gut growth factor.